Thrombin-binding DNA aptamer forms a unimolecular quadruplex structure in solution. - Macaya, R F (1993)
We have used two-dimensional 1H NMR spectroscopy to study the conformation of the thrombin-binding aptamer d(GGTTGGTGTGGTTGG) in solution. This is one of a series of thrombin-binding DNA aptamers with a consensus 15-base sequence that was recently isolated and shown to inhibit thrombin-catalyzed fibrin clot formation in vitro [Bock, L. C., Griffin, L. C., Latham, J. A., Vermaas, E. H. & Toole, J. J. (1992) Nature (London) 355, 564-566]. The oligonucleotide forms a unimolecular DNA quadruplex consisting of two G-quartets connected by two TT loops and one TGT loop. A potential T.T bp is formed between the two TT loops across the diagonal of the top G-quartet. Thus, all of the invariant bases in the consensus sequence are base-paired. This aptamer structure was determined by NMR and illustrates that this molecule forms a specific folded structure. Knowledge of this structure may be used in the further development of oligonucleotide-based thrombin inhibitors.